Normoalbuminuric Diabetic Kidney Disease- Need for Renal Biopsy? An Autopsy Study on Western Indian Population - Paul, Sonal; Gadgil, Nitin M; Padmanabhan, Anitha (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Persistent albuminuria and glomerular filtration rate are considered as the gold standard for the diagnosis of Diabetic Nephropathy (DN). Methods: In this autopsy study, we evaluated data from a cohort of 67 patients with Type 2 Diabetes Mellitus. We determined the histological prevalence of DN irrespective of the clinical manifestations of renal disease. Patients were stratified by proteinuria and estimated glomerular filtration rate(eGFR). The glomerular, interstitial and vascular lesions were scored as per the established histopathologic classification for DN. Results: 55 of the 67 patients had clinical as well as histological lesions consistent with DN. 12 patients had histological lesions of DN at autopsy but no clinical evidence of proteinuria, including microalbuminuria in their lifetime.4 of these patients had maintained eGFR. There was no difference in the glomerular lesions in patients with normoalbuminuria regardless of the eGFR. However,50% of the patients with low eGFR showed presence of interstitial fibrosis and tubular atrophy while no interstitial lesions were noted in patients with normoalbuminuria and maintained eGFR. Significant amount of arteriosclerosis was noted in the normoalbuminuric low eGFR patients. Haematuria was significantly associated with proteinuric low GFR patients. Conclusion: Histological evidence of DN may be seen even in the absence of clinical manifestations, suggesting that, in diabetic kidneys some amount of glomerular and tubulointerstitial damage has already occurred before the onset of proteinuria. Hence, there is a need for routine kidney biopsies in diabetic patients with normoalbuminuria. This will help in the timely diagnosis and appropriate management in the early stages of DN.